Atomistic insights into the degradation of perfluorosulfonic acid membranes: A reactive force field molecular dynamics study - Wanhua Qi; Yang Li; Shifeng Ruan; Xian Gui; Yaoli Xu; Haibin Lu (PLoS ONE, 2026)
The chemical degradation of perfluorosulfonic acid (PFSA) membranes remains a critical barrier to the commercial viability of proton exchange membrane fuel cells (PEMFCs). This study employs reactive force field molecular dynamics (ReaxFF-MD) simulations to elucidate the atomistic-scale mechanisms of degradation initiated by hydroxyl (·OH) and hydrogen (H·) radicals. It is demonstrated that H· radicals preferentially abstract fluorine atoms from the polymer backbone (–CF₂–) and attack terminal carboxyl groups (–COOH), thereby initiating unzipping reactions that result in chain scission and defluorination. In contrast, ·OH radicals predominantly attack sulfonic acid groups (–SO₃H) and tertiary carbon sites, leading to side-chain cleavage with minimal backbone disruption. Mixed radical environments exhibit synergistic degradation kinetics, wherein ·OH-mediated regeneration of H· radicals substantially accelerate membrane failure. Elevated temperatures further exacerbate degradation by reducing activation barriers and enhancing radical mobility. A fundamental trade-off between dielectric properties and chemical stability is identified: although polar functional groups enhance proton conductivity, they simultaneously introduce sites susceptible to radical degradation. Selective passivation of –COOH groups is shown to significantly enhance durability while retaining high proton conductivity. These insights provide a mechanistic foundation for the rational design of degradation-resistant PFSA membranes.